Chronic bronchitis in the 50-year follow-up of the European cohorts of the Seven Countries Study: prevalence, mortality and association with cardiovascular diseases. (May 2021) - Puddu, Paolo Emilio; Menotti, Alessandro; Kromhout, Daan; Kafatos, Anthony; Tolonen, Hanna
Abstract: Objectives: To study prevalence of chronic bronchitis (CB) in residential populations and its relationship with mortality in a 50-year follow-up. Material and methods: In the late 1950's-early 1960's, 7047 men aged 40–59 years were enrolled in 10 European cohorts of the Seven Countries Study (in Finland, the Netherlands, Italy, Serbia and Greece). After baseline examination, follow-up for mortality was extended during 50 years (45 year in the Serbian cohorts). Prevalence of CB, and 50-year mortality from CB and other major causes of death were used as end-points to identify their determinants using multivariate models. Results: Prevalence of CB was directly associated with smoking habits and inversely associated with high socio-economic status (SES), forced expiratory volume in ¾ sec (FEV) and the ratio FEV/vital capacity (VC). Fifty-year mortality from CB was directly predicted by CB prevalence (from a minimum hazard ratio [HR] 2.35, 95% confidence limits [CI] 1.70–3.24, to a maximum HR 3.01, CI 2.18–5.20, depending on diagnostic criteria and different models) and age, and inversely by high SES, FEV and FEV/VC. The same applied in models predicting mortality from coronary heart disease (HR for prevalent CB: 1.53, CI 1.24–1.88), major cardiovascular diseases (HR 1.43, CI 1.23–1.67) and all-cause mortality (HR 1.48, CI 1.34–1.64) all adjusted for age, high SES, smoking habits and FEV. Conclusions: CB is strongly associated with major cardiovascular disease and all-cause mortality while FEV and FEV/VC seem to carry at least partly an independent role from CB in predicting long-term mortality. Highlights: In 7047 middle-aged men, prevalence of chronic bronchitis (CB) was investigated as determinants of 50-year mortality from CB and cardiovascular (CVD) and all-cause deaths. Prevalence of CB was directly associated with smoking habits and inversely associated with high socio-economic status, forced expiratory volume in ¾ sec (FEV) and the ratio FEV/vital capacity (VC). CB was strongly associated with CVD and all-cause mortality while FEV and FEV/VC partly carried an independent role from CB in predicting long-term mortality.